Pengaruh Pengungkapan Corporate Social Responsibility terhadap Profitabilitas (Studi Kasus pada Perusahaan Manufaktur di Bursa Efek Indonesia) - Shahnia, Nurul Ajeng; Davianti, Arthik (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aims to examine the disclosure effect of Corporate Social Responsibility on profitability. Disclosure of economic, environmental, and social aspects of CSR as independent variables, firm size and leverage as control variables, and profitability as dependent variables. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2019 period. The sample selection in this study used a purposive sampling method and obtained 142 sample companies. Multiple linear regression techniques were used for hypothesis testing and the data was processed using Statistical Product and Service Solution Version 20. The results of this study indicate that the disclosure of Corporate Social Responsibility in economic and environmental aspects has no significant effect on company profitability, while disclosure of Corporate Social Responsibility social aspects has a significant positive effect on company profitability.